2017
DOI: 10.1007/s10528-017-9835-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gladiolus Germplasm Using Morphological, Physiological, and Molecular Markers

Abstract: Estimation of variability and genetic relationships among breeding materials is one of the important strategies in crop improvement programs. Morphological (plant height, spike length, a number of florets/spike), physiological (chlorophyll content, chlorophyll fluorescence, and rapid light curve parameters) and Directed amplification of minisatellite DNA (DAMD) markers were used to investigate the relationships among 50 Gladiolus cultivars. Cluster analysis based on morphological data, physiological characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Estimates of PIC, RP and MI signify overall ability of such markers in detecting polymorphisms in the plant population and between any two genotypes or cultivars taken at random from that population, the overall utility of a marker for detecting genetic variation and infer genetic relationships between accessions [30]. In the current study, SSR markers showed comparatively higher polymorphism against those DNA markers used in earlier reports [36, 23,4,43].…”
Section: Marker E Ciency and Allelic Diversity Measuressupporting
confidence: 46%
See 1 more Smart Citation
“…Estimates of PIC, RP and MI signify overall ability of such markers in detecting polymorphisms in the plant population and between any two genotypes or cultivars taken at random from that population, the overall utility of a marker for detecting genetic variation and infer genetic relationships between accessions [30]. In the current study, SSR markers showed comparatively higher polymorphism against those DNA markers used in earlier reports [36, 23,4,43].…”
Section: Marker E Ciency and Allelic Diversity Measuressupporting
confidence: 46%
“…Application of molecular markers for germplasm characterization, conservation and crop improvement of gladiolus is very limited despite its popularity. In previous reports, molecular markers such as RAPD -Random Ampli ed Polymorphic DNA [23,36], ISSR -Inter Simple Sequence Repeats [4,37,43], SCAR -Sequence Characterized Ampli ed Region [19,41] and AFLP -Ampli ed Fragment Length Polymorphism [18,36,46] have been utilized for the assessment of genetic diversity and phylogeny of gladiolus species and cultivars. However, more reliable and easily reproducible markers like SSRs (Simple Sequence Repeats) are meagre in gladiolus.…”
Section: Introductionmentioning
confidence: 99%
“…1). Hossain et al (2011) recorded more or less similar range of 46.52-58.65 cm plant height in the studied genotypes of gladiolus; whereas, Singh et al (2017) recorded a range from 80.3-134.7 cm plant height with a mean of 112.0 cm in ten hybrids of gladiolus. As the genotypes of present study has been collected from farmers field and they are hopefully open pollinated; so, the variation in plant height of different gladiolus genotypes might be due to the genetic difference as well as growing environment and management practices.…”
Section: Resultsmentioning
confidence: 76%
“…Phenotypic variability among the Gladiolus cultivars is extensive and is caused by genetic, environmental, and physiological factors (Singh et al, 2017b). Due to high conservation of miRNA sequences was developed an effective type of molecular markers useful not only for genetic diversity studies but also for functional polymorphism analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The most applied molecular markers used for the evaluation of genetic diversity and population structure of gladioulus are ISSR (Inter Simple Sequence Repeats), DAMD (Directed Amplification of Minisatellites) and RAPD-derived SCARS (Random Amplified Polymorphic DNA-derived Sequence-Characterised Amplified Region) markers (Kumar et al, 2016;Singh et al, 2016Singh et al, , 2017aSingh et al, , 2017bSingh et al, , 2018Chaudhary et al, 2018).…”
Section: Introductionmentioning
confidence: 99%